A survey research of reading methods used by New Mexico middle school teachers - Martinez, Sylvia Ann (Kansas State University, 2007)
The purpose of the study was to determine the reading methods New Mexico teachers considered important to use in their classrooms and schools. Design of the study was based on a fixed goals COBRA (content-based reading approach) model, which is in development by Heerman (2002). The New Mexico COBRA model was revised to fit the socio-cultural context of the diverse student population served by middle schools in the state. Teachers in New Mexico were asked to respond to a reading survey built around 44 reading methods distributed among seven goals of the COBRA model. The researcher surveyed 153 New Mexico middle school educators in 110 middle school building in order to determine the relative emphasis placed on various reading methods. A revision of the original survey used by Al-Fadda was conducted, which included drafting ELL survey items used at the middle schools with reference to culturally and linguistically diverse students or ELLs. Five research questions were used to build the rationale for the COBRA framework, develop the survey, conduct the survey research, and analyze the results. Middle schools included in this survey research were characterized as middle schools with a student population of 200 and above. The pool of educators asked to participate in the survey taught or were involved with the reading program at their respective schools. These included reading teachers, English language arts teachers, Bilingual/ESL/TESOL teachers, and instructional and school improvement leaders familiar with the building’s reading program. These middle level teachers perceive as important a first line conventional framework for middle level reading, which includes skills instruction, narrative literature instruction, and writing. These teachers give first emphases to reading instruction and communicative competence while content reading instruction is a secondary emphasis.
Keywords: Reading; English as a Second Language; COBRA model; Content reading infusion; New Mexico; English Language Learners; Education, Bilingual and Multicultural (0282); Education, Reading (0535)